PENGARUH MATERIAL DINDING SEMEN ECENG GONDOK TERHADAP PENYERAPAN SUARA (FUNGSI AKUSTIK) - Iffandani, Winodianto Dodi (Department of Civil Engineering, Faculty of Engineering, University of Muhammadiyah Malang, 2012)
‘Eceng Gondok’ was still considered as troubled weeds plant, since the growth was so fastand in 3-4 months able to cover more than 70% water surface.The research was done in Civil Engineering Laboratory University of Muhammadiyah Malangby prototype placement south area of University of Muhammadiyah Malang stadium. Compoundmaterial with ‘Eceng Gondok’ compound material : glue : cement was 1:1:2.5. Test was done in 3sound sources 80 dB, 85 dB, and 90 dB.Test which was done to wall prototype was bounce back sound, escape sound, and soundabsorption to eceng gondok wall by comparing to brick wall prototype with similar test. From testand calculation, there found average value for eceng gondok wall was not better in sound absorptionwith brick wall > eceng gondok wall in sound source 80 dB, 85 dB, and 90 dB found 31.63 > 28.96dB, 36.64 > 30.06 dB, 39.81> 29.95 dB. eceng gondok wall was better for escape sound with valuebrick wall < eceng gondok wall in sound source 80 dB, 85 dB, and 90 dB found 39.86 < 42.46 dB,39.68 < 46.34 dB, 41.46 < 51.63 dB. And eceng gondok wall could be similar in echo sound withsignificance 5% at the sound source 80 dB, 85 dB, and 90 dB.Keywords: cement wall, ‘Eceng Gondok’, sound absorption (acoustic)